Superovulation combined with insemination or timed intercourse in the treatment of couples with unexplained infertility and minimal endometriosis - Rita Isaksson; Aila Tiitinen (Acta Obstetricia et Gynecologica Scandinavica)
Background. To compare intrauterine insemination (IUI), direct intraperitoneal insemination (DIPI), and timed intercourse (TI), each combined with superovulation, in the treatment of couples with unexplained infertility, including couples with minimal endometriosis. Methods. A retrospective analysis of 233 superovulation cycles in 70 couples with unexplained infertility or minimal endometriosis. Stimulation protocol, pregnancy rate, pregnancy outcome, and complications of treatment were analyzed. Results. The pregnancy rare was 8.6% per cycle and 28.5% per couple. A majority of all treatment pregnancies (85%) occurred during the first four cycles of treatment. The duration of infertility did not influence the pregnancy rate. The pregnancy rate in patients with unexplained infertility was higher, but not significantly, than in patients with minimal endometriosis (27.7% versus 18.4%). No predictive marker for successful stimulation was found, except for the higher luteal progesterone level in cycles resulting in pregnancy. The multiple pregnancy rate was high: 30% of all pregnancies and 40% of all deliveries were multiple. Conclusions. Superovulation in combination with insemination or intercourse is effective and is still recommended in the treatment of couples with unexplained infertility.